Communicating for a change - Stanley, Andy.; Jones, Lane. (Sisters, Or. : Multnomah Publishers, 2006)
Whether you speak from the pulpit, podium, or the front of a classroom, you don't need much more than blank stares and faraway looks to tell you you're not connecting. Take heart before your audience takes leave! You can convey your message in the powerful, life-changing way it deserves to be told. An insightful, entertaining parable for communicators, How's My Preaching? takes a simple approach to delivering effectively. Join Pastor Ray as he discovers the secrets to successful speaking are parallel to the lessons a trucker learns on the road. By knowing your destination before you leave (identifying the one basic premise of your message), using your blinkers (making transitions obvious), and implementing five other practical points, you'll drive your message home every time!
No one's listening -- Where there's a will there's a ray -- Go for the goal -- The end of the road -- A map to remember -- Load up before you leave -- Crucial connections -- Show me some identification -- Stuck in the middle of nowhere -- A new attitude -- Determine your goal -- Pick a point -- Create a map -- Internalize the message -- Engage your audience -- Find your voice -- Start all over.
Includes bibliographical references (p. 199).
Keywords: Communication -- Religious aspects -- Christianity; Preaching